Effects of discourse force, sentence importance, and claim type on comprehension and recognition - Pounds, Julia C. (Kansas State University, 1992)
Studies of discourse have not resolved the question of whether different types of texts are comprehended and remembered differently. To clarify this question the present study used three print message forms (business memoranda, personal letters, and newspaper advertisements) used in other studies. Direct assertions and pragmatic implications were embedded in constructed messages. The stimulus sentences were independently rated as more important or less important to the message. Subjects rated truth-value while reading and again in a recognition task. Results indicated that the form in which the message appeared, the claim type in which the sentence was written, and the importance of the sentence to its text influenced truth-value ratings. The commonly held notion that people do not believe advertising was evident when subjects were reading. Results suggest that studies of message miscomprehension need to account for how subjects perceive the intention of the writer and how this perception influences the inferences readers make about the message.